2021
DOI: 10.1186/s12987-021-00266-z
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences in the localization, trafficking, and function of P-glycoprotein in MDR1-EGFP-transduced rat versus human brain capillary endothelial cell lines

Abstract: Background In vitro models based on brain capillary endothelial cells (BCECs) are among the most versatile tools in blood–brain barrier research for testing drug penetration into the brain and how this is affected by efflux transporters such as P-glycoprotein (Pgp). However, compared to freshly isolated brain capillaries or primary BCECs, the expression of Pgp in immortalized BCEC lines is markedly lower, which prompted us previously to transduce the widely used human BCEC line hCMEC/D3 with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 96 publications
(179 reference statements)
0
3
0
Order By: Relevance
“…Hence, it is mandatory that a high-throughput and low-cost alternative for excessive animal testing demonstrates Pg-p expression. However, it was previously demonstrated that wild-type hCMEC/D3 cells exhibit a low expression of Pg-p and low junctional tightness under routine culture conditions [ 56 ]. For this, we studied the percentage of positive cells expressing P-glycoprotein (CD243), PECAM-1 (CD31), ICAM-1 (CD54), transferrin receptor (CD71) and CD45 in the static BBB model as well as the dynamic TripleB model using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is mandatory that a high-throughput and low-cost alternative for excessive animal testing demonstrates Pg-p expression. However, it was previously demonstrated that wild-type hCMEC/D3 cells exhibit a low expression of Pg-p and low junctional tightness under routine culture conditions [ 56 ]. For this, we studied the percentage of positive cells expressing P-glycoprotein (CD243), PECAM-1 (CD31), ICAM-1 (CD54), transferrin receptor (CD71) and CD45 in the static BBB model as well as the dynamic TripleB model using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…A potential drawback of tagging a protein is that the tag may affect the structure of the protein, and thereby, alter its function. However, to reduce the potential effects of the tag on protein behavior, the tag was attached to the C‐terminus of the protein as has been done in previous reports studying P‐gp (Chen et al, 2001; Chen & Simon, 2000; Gericke et al, 2021). Additionally, we included a linker to tag the P‐gp orthologs to permit some flexibility in the structure and minimize any steric interference on protein function.…”
Section: Discussionmentioning
confidence: 99%
“…There can be concerns when inducing expression of proteins that abnormal cellular distributions may occur. Gericke et al [21] have examined this for P-glycoprotein in brain endothelial cell lines in vitro.…”
mentioning
confidence: 99%